2018
DOI: 10.1177/0731948718769248
|View full text |Cite
|
Sign up to set email alerts
|

Studying Virtual Manipulatives Paired With Explicit Instruction to Teach Algebraic Equations to Students With Learning Disabilities

Abstract: Over the last two decades, the significance of academic achievement for students with disabilities in K-12 education has increased. To meet the needs of this population, educators turned to innovative strategies and technologies for instructional support in the classroom. For students with a learning disability, the need for such solutions is vital to address many of the academic struggles they face in the area of mathematics education. One evidence-based strategy shown to support instruction for students with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…In three studies, five out of 12 students qualified for free or reduced‐price lunch or were of below average SES. Only one study reported the participants’ English learner status (Satsangi, Hammer, Hogan, 2018). Regarding setting, three studies took place in vacant classrooms, three in a conference or supply room, one in two math classrooms, one in a resource classroom, and one in an office; three studies did not specifically report the setting.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In three studies, five out of 12 students qualified for free or reduced‐price lunch or were of below average SES. Only one study reported the participants’ English learner status (Satsangi, Hammer, Hogan, 2018). Regarding setting, three studies took place in vacant classrooms, three in a conference or supply room, one in two math classrooms, one in a resource classroom, and one in an office; three studies did not specifically report the setting.…”
Section: Resultsmentioning
confidence: 99%
“…Across domains, studies reflected between one and four content standards within their studies. Specifically, 8 of the 12 studies reflected one content standard, two studies (Hunt & Vasquez, 2014; Satsangi, Hammer, Hogan, 2018) reflected two content standards, one study reflected three content standards (Hutchinson, 1993), and one study (Park & McLeod, 2018) reflected four content standards.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale for the CRA sequence is development of conceptual understanding of numbers and operations. Research shows that CRA instruction is effective in teaching complex computation such as addition with regrouping (Bouck, Park, Shurr, Bassette, & Whorley, 2018; Miller & Kaffar, 2011), subtraction with regrouping (Bouck, Chamberlain, & Park, 2017; Flores & Hinton, 2019; Mancl, Miller, & Kennedy, 2012), and algebra (Satsangi, Hammer, & Hogan, 2018; Witzel, 2005; Witzel, Mercer & Miller, 2003). CRA computation interventions included the Strategic Instruction Model (SIM) to assist in developing procedural knowledge, but only after students achieve conceptual understanding.…”
Section: Concrete Representational Abstract (Cra) and Two‐digit Multimentioning
confidence: 99%